Zakah Economic Concept in the Determination of Pricing on Islamic Banking Products - Riris Aishah Prasetyowatir; Muhammad Said (International Journal of Supply Chain Management, 2017)
Abstract- Determining the selling price and the purchasing price in Islamic banking products has attracted much attention in the post-crisis discussion of how to make the Islamic financial system more firmly running the principles of sharia. This paper investigates and calibrates a Pricing Model Islamic Bank. The model Pricing is adopted from the simple model of general equilibrium. We argue that the theory of consumption inters temporal Islam namely: Islam executed by the community, Zakat is obligatory, No usury in the economy. We argue that, has its own pricing model defeat interest rate provisions of the central bank in positive states of the Islamic Economy. They would have been in a better position to set prices. The allowances accumulated by means of themaximize the zakah for the welfare of the people. That the Islamic pricing model proposed expected into consideration by regulator.